2019
DOI: 10.1111/ele.13272
|View full text |Cite
|
Sign up to set email alerts
|

Habitat fragmentation reduces plant progeny quality: a global synthesis

Abstract: Most of the world's land surface is currently under human use and natural habitats remain as fragmented samples of the original landscapes. Measuring the quality of plant progeny sired in these pervasive environments represents a fundamental endeavour for predicting the evolutionary potential of plant populations remaining in fragmented habitats and thus their ability to adapt to changing environments. By means of hierarchical and phylogenetically independent meta‐analyses we reviewed habitat fragmentation eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
129
3
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 143 publications
(160 citation statements)
references
References 105 publications
5
129
3
4
Order By: Relevance
“…cpDNA can reveal a more highly geographical structure than a nuclear genome [17] and is generally used in the detection of phylogeographical patterns in plant species [18,19]. Thus, nSSRs and cpDNA were extensively and successfully documented to study the genetic diversity, variation, and population demographic of plant species [17,[20][21][22].Habitat loss and destruction are global problems that continue to threaten global biodiversity [23,24]. Firstly, habitat destruction and loss can cause a decline in the distribution range and population and limit the natural regeneration of a species.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…cpDNA can reveal a more highly geographical structure than a nuclear genome [17] and is generally used in the detection of phylogeographical patterns in plant species [18,19]. Thus, nSSRs and cpDNA were extensively and successfully documented to study the genetic diversity, variation, and population demographic of plant species [17,[20][21][22].Habitat loss and destruction are global problems that continue to threaten global biodiversity [23,24]. Firstly, habitat destruction and loss can cause a decline in the distribution range and population and limit the natural regeneration of a species.…”
mentioning
confidence: 99%
“…Finally, habitat destruction and loss increase genetic drift and inbreeding and reduce gene flow in the fragmented populations of species and substantially decrease species genetic diversity and adaptation to the changing environment. Some studies suggested that woody plants are less likely to lose genetic diversity after habitat fragmentation and destruction than herbaceous species [26]; however, recent reports showed that habitat loss and fragmentation are associated with increased level of inbreeding, reduced gene flow, genetic variation, plant progeny quality, and genetic extinction debt in woody species [24,27]. Thus, understanding the current genetic information of endangered woody plants subjected to habitat loss and destruction is necessary for effective conservation and management.Rhododendron species are not only popular woody ornamental plants but also play an important role in alpine and subalpine ecosystems.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Since our results are largely unbiased by the effect of habitat fragmentation, the underlying genetic structure of plant populations, the resolution of spatial data, or time-lag effects, they reveal that habitat loss does not always entail negative genetic consequences. Although habitat fragmentation has been shown to disrupt gene flow and increase inbreeding across plants species, regardless of their characteristics (Aguilar et al, 2019), our study unveils remarkably resilient species to extreme habitat loss as similar levels of genetic diversity and gene flow were found in mining and natural habitats. These findings imply that it is not possible to generalize about Genetic consequences of habitat loss Supplementary Tables S3 and S5 for details).…”
Section: Discussionmentioning
confidence: 56%
“…given that the progeny of insect-and wind-pollinated plants has been shown to be strongly negatively affected by habitat fragmentation (Aguilar et al, 2019). Relying on genotyping-by-sequencing of hundreds of individuals from both species collected across these two mining landscapes, we assessed the influence of habitat loss on genetic diversity and gene flow.…”
Section: Genetic Consequences Of Habitat Lossmentioning
confidence: 99%